Storage Temperature of Botanical Insecticide Mixture Formulations and Its Activity Againsts Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) - Eka Candra Lina; Nia Yulianti; Gustria Ernis; Arneti Arneti; Novri Nelly (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
The purpose of this research was to evaluate the safety of mixture formulations of Tephrosia vogelii and Piper aduncum at various storage temperatures and their insecticidal activity against C. pavonana larvae. Formulations were made from T. vogelii and P. aduncum (1:5) in emulsifiable concentrate (EC) and wettable powder (WP) form. Both formulations have strong insecticidal activity against C. pavonana. This research used a randomized completed design in different temperature treatments. Insecticidal activity of formulations after storage was tested against C. pavonana. The treatments were done using deep leaf method in 5 concentrations and 5 replications. The results showed that LC95 value of EC formulation after storage at condition: below 4°C, room temperature, and 40°C were 0.19%, 0.34% and 0.21% respectively. Based on LC95 value of EC formulation from each treatment, indicated that EC formulation after storage could hold insecticidal activity as good as insecticidal activity before storage due to LC95 value after storage relatively lower than LC95 value before storage (0.35%). In the contrary, WP formulation activity was significantly decreased in all treatments compared to WP formulation activity before storage based on LC95 value.